Pelatihan Perencanaan Dan Pengelolaan Keuangan Pribadi Pada Santri Pondok Pesantren Mahasiswa Jagad ‘Alimussirry Surabaya - Khusnah, Hidayatul; Mardiyah Anugraini; Mohamad Yusak Anshori (JCSE: Journal of Community Service and Empowerment, 2022)
This community service activity is carried out to increase knowledge and understanding of personal financial management. Financial literacy education is not found in the curriculum at the University, even though this education is very important in financial planning now and in the future. Financial literacy occurs when an individual has a set of skills and abilities that make that person able to utilize existing resources to achieve goals. Through this community service activity, training activities and seminars on the basics of finance were initiated to improve financial literacy among the community. The target audience who will be trained in this activity are the students of the Jagad ‘Alimussirry Islamic Boarding School Surabaya.